CROSSWORD PUZZLE GAME FOR TEACHING VOCABULARY - Impiani Zagoto; Renata R. S. A. Laia (Universitas Nias Raya, 2022)
Improving students’ vocabulary mastery using Crossword Puzzle Game was the aim of this research. This research was designed by using Classroom Action Research (CAR) which was done in two cycles. The subject of this research was the Eighth Grade Students of SMP Negeri 1. The instruments of collecting the data were observation paper and test. The result of data analysis showed that the result of the researcher’s observation paper in the cycle I for the first meeting was 73.68% while in the second meeting was 85.71%. In the cycle II for the first meeting was 88.23% and the second meeting was 100%. The result of students’ observation paper on the cycle I for the first meeting was 65.93% and the second meeting was 71.43%. In the cycle II for the first meeting was 87.91% and the second meeting was 98.02%. Furthermore, the average score of the students’ test result in cycle I was 40.95 while the average score of students’ test result in cycle II was 75. Based on the findings, it is concluded that the implementation of Crossword Puzzle Game is useful to teach vocabulary since it offered a good exercise to help the students to understand and learn different levels of meaning for the same words. In addition, it is suggested to the English teacher to apply Crossword Puzzle Game in teaching English vocabulary and for another researcher as a reference in doing research.